Description of the second juvenile stage of the blue-fingered burrowing crayfish Parastacus caeruleodactylus (Decapoda: Astacidea: Parastacidae) - Ribeiro, Felipe Bezerra; Gomes, Kelly Martinez; Huber, Augusto Frederico; Araujo, Paula Beatriz (Zootaxa, 2019)
This study describes and illustrates the morphology of the second juvenile stage of the blue-fingered burrowing crayfish Parastacus caeruleodactylus. One female carrying 20 juveniles was collected in January 2019 from a swamp forest in the municipality of Dom Pedro de Alcântara, state of Rio Grande do Sul, southern Brazil. Juveniles were dissected and the appendages were mounted in slides. The general morphology and the pattern of attachment of the second juvenile stage of P. caeruleodactylus correspond to that reported for other parastacids. The main differences among the co-generic species are related to the number of articles in the flagella of the antennae, the number of spines in the antennal scale, the number of setae in the articles of the appendages, the number of teeth in the mandible molar and incisor processes, the absence of segmentation in the exopod flagellum of the maxillipeds and the number of teeth in the crista dentata of the ischium of maxilliped 3.